Hydrothermal Preparation of Gd3+-Doped Titanate Nanotubes: Magnetic Properties and Photovoltaic Performance - Hoda S. Hafez; M. Saif; James T. McLeskey,; M. S. A. Abdel-Mottaleb; I. S. Yahia; T. Story; W. Knoff (International Journal of Photoenergy)
Pure and Gd3+-doped titanate nanotubes (TNTs) materials were synthesized by a hydrothermal method. Their morphology, optical properties, thermal stability, and magnetic properties were characterized by X-ray diffraction (XRD), transmission electron microscope (TEM), UV-Vis spectroscopy, thermal analysis, and magnetic measurements. It was found that doping renders Gd3+-TNT visible light active and results in smaller crystallite size and larger surface area as well as higher thermal stability compared to pure titanate nanotubes. The estimated magnetic moments point to presence of weak antiferromagnetic interaction. Application of the prepared Gd3+-TNT for modifying conventional photoanodes in polymer solar cells was attempted. Preliminary results show slightly improved photovoltaic energy conversion efficiency in the devices containing the newly designed Gd3+-doped nanotubes.